2021
DOI: 10.1073/pnas.2021359118
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of introducing and lifting nonpharmaceutical interventions on COVID-19 daily growth rate and compliance in the United States

Abstract: We evaluate the impacts of implementing and lifting nonpharmaceutical interventions (NPIs) in US counties on the daily growth rate of COVID-19 cases and compliance, measured through the percentage of devices staying home, and evaluate whether introducing and lifting NPIs protecting selective populations is an effective strategy. We use difference-in-differences methods, leveraging on daily county-level data and exploit the staggered introduction and lifting of policies across counties over time. We also assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 18 publications
(25 reference statements)
8
65
0
Order By: Relevance
“…Regarding the impact of policy change on the COVID-19 transmission, our findings are consistent with previous studies. Studies have reported that policies, such as school closure, shelter-in-place orders, bans on large social gatherings, were associated with a significant decline in the incidence of COVID-19 in the U.S. [47][48][49][50]. In our study, most of the districts observed a similar impact of policies on the COVID-19 transmission.…”
Section: Power-law Relationship Between Cumulative Case Count and Population Sizesupporting
confidence: 71%
See 1 more Smart Citation
“…Regarding the impact of policy change on the COVID-19 transmission, our findings are consistent with previous studies. Studies have reported that policies, such as school closure, shelter-in-place orders, bans on large social gatherings, were associated with a significant decline in the incidence of COVID-19 in the U.S. [47][48][49][50]. In our study, most of the districts observed a similar impact of policies on the COVID-19 transmission.…”
Section: Power-law Relationship Between Cumulative Case Count and Population Sizesupporting
confidence: 71%
“…A small difference in the transmission can be attributed to several factors, such as population size, urbanization, and demographic factors. A study by Singh et al (2021) found that policies were more effective in counties with nonWhite populations, possibly due to a wider spread shutdown of businesses, and in counties with a higher median household income that can be attributed to potential stronger compliance, due to having more flexibility to work remotely in these counties [49].…”
Section: Power-law Relationship Between Cumulative Case Count and Population Sizementioning
confidence: 99%
“…At the beginning of the COVID-19 pandemic, at exoand macrosystem levels, non-pharmaceutical public health interventions were implemented to slow the spread of the virus (Mervosh et al, 2020;Singh et al, 2021) and there was uncertainty about the virus and potential duration of the pandemic (Koffman et al, 2020). Menter et al (2020) explained:…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This study adds to a growing literature that has examined the effect of NPIs on the number of COVID-19 cases, deaths, and social distancing behaviors. Some existing studies have used cellular phone mobility tracking and have found that the implementation of SIP policies leads to small changes in mobility with weaker effects on mobility in the U.S. compared to Europe (Berry et al 2021;Singh et al 2021;Askitas, Tatsiramos, and Verheyden 2021;Xu 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within the U.S. context, there were important differences based on income, with larger increases in physical distancing for individuals in high-income neighborhoods than individuals in lowincome neighborhoods (Jay et al 2020;Singh et al 2021).…”
Section: Literature Reviewmentioning
confidence: 99%